Reducing Water Scarcity by Reducing Food Loss and Waste - Marston, Landon T.; Read, Quentin D.; Brown, Samuel P.; Muth, Mary K. (Frontiers in Sustainable Food Systems, 2021)
Water scarcity is a pervasive threat to society that is expected to intensify alongside a growing and more affluent population and a changing climate. In this paper, we review the existing literature to assess the potential of lessening water scarcity by reducing food loss and waste. Existing studies reveal the scope of food loss and waste and its accompanying impact on water resources, thereby providing a foundation for policy action. We highlight existing or proposed food loss and waste reduction measures and review available evidence concerning their impact on water resources. Our review reveals that there is a deficit of research that can guide specific policy interventions aimed at mitigating water scarcity by reducing food loss and waste. Instead, the last decade of research has primarily focused on quantifying the current water footprint of food loss and waste for different locations, points within the supply chain, and food groups. Yet, the degree of uncertainty inherent in these estimates, their lack of precision, and several simplifying assumptions make it difficult to translate this research into robust policy measures to reduce the environmental burden of food loss and waste. We conclude by advancing a research agenda that will i) quantify and reduce uncertainty through enhanced data collection and methods; ii) holistically assess policy measures, including system level impacts and feedback; iii) developing methods and technologies for transparent supply chain tracing. Together, advances in these areas will guide and ground food loss and waste policy towards reducing water scarcity.